The impact of functional integration between graphic design and signage systems in enhancing the visitor experience at archaeological sites City "Jerash"–Jordan (Architecture Image Studies, 2025)
This research aims to study the impact of functional integration between graphic design and wayfinding systems in enhancing the visitor experience within archaeological sites in the Hashemite Kingdom of Jordan, with a focus on developing a smart hybrid guidance system that combines physical signage with modern digital technologies, including QR, NFC, and smart maps, to facilitate access to information and improve the overall visitor experience.The research relied on a descriptive, analytical, and experimental approach to analyze old wayfinding systems at archaeological sites, assess their strengths and weaknesses, evaluate their compliance with international standards in wayfinding system design, and design a new interactive practical experience. The 2020 master's thesis questionnaire by researcher Mohamed Al-Afif was used to assess visitor satisfaction with the existing guidance system, which has not undergone any development to date. The results showed low to moderate satisfaction due to poor coordination between officials, designers, and implementers, lack of maintenance, and the use of materials unsuitable for the nature of the site. This data formed the basis for developing the research and designing an integrated guidance model that takes into account the needs of visitors and the historical character of the site. The study concluded that enhancing the visitor experience at archaeological sites requires an integrated guidance system that combines modern graphic design with interactive technologies such as QR Codes and NFC. This system provides clear information and accurate guidance, creating an enjoyable interactive experience that includes digital maps and visual and audio content. The adoption of uniform design standards and durable materials ensures the sustainability and efficiency of the system, while promoting collaboration between designers and officials to develop the system in line with visitor needs and contemporary technologies.